Detection phishing Attacks Using Emerging Technologies - Shaik Naazmeen, Derangula Bhagyasree, G. RamakoteswaraRao, Julakanti Tejeswar (International Journal of Advanced Science and Technology, 2020)
In today’s world, every person’s part of life is attached to the internet from there professional life to personal life. The internet has taken a wide range of impact in the world. The internet is useful not only for good but also to hackers, attackers, etc., these types of people are called phishers. Who seeks information about others with or without people’s knowledge? There are different types of phishing attacks they are social engineering, shouldering, key loggers, etc., In this paper, we are about to show different technical ways of finding whether a site is phished or not. One is we are using machine learning algorithms of 4 different kinds. They are decision tree, SVM, Random forest, Logistic regression. The results are based on accuracy. All of them are compared and the algorithm which has the highest is suggested to use during phishing attacks. Second, we are using different tolls to show which one gives better domain information about the phished site. They are WHOIS, MX Tool box, Phish Tank. And a technique is used i.e., counter phishing which demonstrates the effects of phishing.